Complexity of temperature‐dependent Raman spectra and phonons properties on the example of carbon nanotubes thin films. (22nd June 2020) - Gertych, A.P.; Czerniak‐Łosiewicz, K.; Żerańska‐Chudek, K.; Dużyńska, A.; Zdrojek, M.; Judek, J.
Abstract: We examine the interplay between intrinsic phonon properties, the variability of material properties, and instrumental uncertainty reflected in temperature‐dependent Raman spectra of inhomogeneous thin films made of two types of carbon nanotubes (metallic and semiconducting), employing statistical Raman mapping. First, we show that the contribution of temperature to Raman peaks properties representing given phonons depends on how the heat is delivered to the sample—global versus local laser heating. We also show that the variability of Raman peaks positions and widths is not negligible and can be separated into instrumental uncertainty and intrinsic material contribution. Finally, we discuss how temperature can affect different correlations and trends in Raman experiments (e.g., the influence of incident laser power on Raman temperature coefficient). Our findings can be useful for improving the reliability of Raman study for various classes of materials, including exfoliated 2D materials, free‐standing thin films made of 2D flakes, or even bulk materials—not only carbon‐based. Abstract : The study of temperature‐dependent Raman spectra is a convenient method for investigating many material characteristics, such as crystal potential or thermal properties. In this work, we employ statistical Raman mapping on inhomogeneous carbon nanotubes thin films to study contribution from local and global heating on Raman spectra. We show that the variability of Raman peaks positions can be separated into material contribution and instrumental uncertainty and discuss how temperature can affect different correlations and trends in Raman experiments.